2015
DOI: 10.5194/bgd-12-1689-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disruption of metal ion homeostasis in soils is associated with nitrogen deposition-induced species loss in an Inner Mongolia steppe

Abstract: Abstract. Enhanced deposition of atmospheric nitrogen (N) resulting from anthropogenic activities has negative impacts on plant diversity in grassland ecosystems globally. Several mechanisms have been proposed to explain the species loss. Ion toxicity due to N deposition-induced soil acidification has been suggested to be responsible for species loss in acidic grasslands, while few studies have evaluated the role of soil-mediated homeostasis of ions in species loss under elevated N deposition in alkaline grass… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Nitrogen (urea) was applied by hand annually in July every year since 2004 when maximal precipitation occurs. Our previous results showed that the applications of urea caused a significant increase in soil nitrate concentrations (Tian et al., 2015), because urea is successively transformed into ammonia/ammonium and nitrate by urease and nitrification. Therefore, urea addition can simulate soil N enrichment caused by atmospheric N deposition.…”
Section: Methodsmentioning
confidence: 97%
See 4 more Smart Citations
“…Nitrogen (urea) was applied by hand annually in July every year since 2004 when maximal precipitation occurs. Our previous results showed that the applications of urea caused a significant increase in soil nitrate concentrations (Tian et al., 2015), because urea is successively transformed into ammonia/ammonium and nitrate by urease and nitrification. Therefore, urea addition can simulate soil N enrichment caused by atmospheric N deposition.…”
Section: Methodsmentioning
confidence: 97%
“…The atmospheric bulk N deposition in this area is approximately 15.1 kg N ha −1 year −1 (Xu et al., 2015). Detailed soil properties in this area were described in our previous study (Tian et al., 2015). The vegetation comprises common forbs ( Artemisia frigida , Potentilla acaulis , Potentilla bifurca , Potentilla tanacetifolia , Allium bidentatum ), sedges ( Carex korshinskyi ) and common grasses ( Stipa krylovii , Leymus chinesis , Agropyron cristatum , Cleistogenes squarrosa ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations